SKRINING FITOKIMIA DARI EKSTRAK BUAH BUNCIS (Phaseolus vulgaris L) DALAM SEDIAAN SERBUK - Rizki Nugrahani; Yayuk Andayani; Aliefman Hakim (Jurnal Penelitian Pendidikan IPA, 2016)
research on the phytochemical screening of extracts of fruit powder beans (Phaseolus vulgaris L). The aims study was determine the content of chemical compound in extract beans that had undergone a process of heating at high temperature and has been stored in a specified time. Classified of chemical compounds would be included flavonoids, alkaloids, phenols, saponins, tannins, steroids and triterpenoids. Results of phytochemical screening showed bean extract contains the chemical compound class of flavonoids, alkaloids, phenols, saponins, steroids and triterpenoids. Keyword: Phytochemic al screening, bean fruit extracts